European Yearbook on Human Rights 2021 - Czech, Philip (Cambridge : Intersentia, 2021)
The European Yearbook on Human Rights brings together renowned scholars, emerging voices and practitioners, comprising contributions which engage with some of the most important human rights issues and developments in Europe. The Yearbook helps to better understand the rich landscape of the European regional human rights system and is intended to stimulate discussions, critical thinking and further research in this field.
Title from publisher's bibliographic system (viewed on 22 Feb 2022).
Keywords: Human rights -- European Union countries -- Periodicals